Penyuluhan Pelatihan Pupuk Kompos Organik di Desa Nolokerto Untu Efisiensi Sampah UMKM Oleh KKN MIT UIN Walisongo - Ukhti Lutfia Khadijah; Rania Tawar Malahayati; Rishma Fajri Choirina; Syahida Shofianti; Faza Naila Fathimatuz Zahra (Lembaga Pengembangan Kinerja Dosen, 2024)
Nolokerto Village is a developing village and most of the businesses owned by the village, one of which is a catering business, produce a lot of organic waste that has a high water content, especially those that are easily decomposed. Unmanaged organic waste can cause environmental problems. Realizing the importance of effective waste management, KKN UIN Walisongo Semarang students held counseling and compost training activities so that food waste can be processed and reused. The program began with general materials on waste, followed by training on compost fertilizer for organic waste. The resulting compost fertilizer is then distributed to villagers to support agriculture and reduce the environmental impact of organic waste.